It's time to complete community college : student outcome studies show what it takes to succeed - Chandler, S. deBoef, 1956- (Rowman & Littlefield, 2018)
"At least half of all college students in the U.S. today attend two-year colleges; yet, fewer than half of these students achieve their educational goals. This book, written by an experienced community college teacher summarizes specific evidence-based methods to improve student learning and completion"--